IC-MEG: Um Checklist Específico para Avaliação de Jogos Educacionais Digitais em Plataformas Móveis - FRAZÃO, Kastney Albuquerque (2021)
Digital educational games for mobile devices have become increasingly present in educa tional environments, where they have gained a lot of relevance in the educational and professional training of many people. These software are present in online app stores, where there is a specific place for their users to review the apps in the catalogs. Despite all the benefits that digital educational games have; these software still have quality problems pointed out by users. Problems in various areas, such as: the usability and functionality of the games; little adherence to the proposal and gameplay; besides, difficulty in supporting and mobility of games on users’ mobile devices. Several technologies for evaluating software have been proposed; however, there is still a need for research development to evaluate specific digital educational games for the mobile platform, while supporting software engineers in detecting defects in the evaluated games. This master’s thesis proposes an inspection checklist for the evaluation of digital educational games for mobile devices called IC-MEG, a support tool called TIMEG was also developed to provide support to the developed checklist; these technologies were developed to support development teams in evaluating their mobile digital educational games. We evaluated the acceptance of IC-MEG and TIMEG from the perspective of novice software engineers in an experimental study. When compared to mGBL and PHEG, other checklists in the literature, the results showed that the IC-MEG was perceived as useful and more complete. In addition, software engineers found the TIMEG tool useful and easy to understand, while suggesting improving its report to make it easier to understand and increase its use. The results of the experimental study indicated users’ satisfaction in reporting their experience with the IC-MEG checklist, while members of the development team agreed with the usefulness of the TIMEG report and its suggestions for improvement. By providing inspection support, we intend to support software engineers in the detection of defects in digital educational games for mobile devices developed, thus increasing their quality and acceptance in the market.